2019
DOI: 10.1104/pp.19.00206
|View full text |Cite
|
Sign up to set email alerts
|

Deetiolation Enhances Phototropism by Modulating NON-PHOTOTROPIC HYPOCOTYL3 Phosphorylation Status

Abstract: Phototropin (phot) receptor kinases play important roles in promoting plant growth by controlling light-capturing processes, such as phototropism. Phototropism is mediated through the action of NON-PHOTOTROPIC HYPOCOTYL3 (NPH3), which is dephosphorylated following phot activation. However, the functional significance of this early signaling event remains unclear. Here, we show that the onset of phototropism in dark-grown (etiolated) seedlings of Arabidopsis (Arabidopsis thaliana) and tomato (Solanum lycopersic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 66 publications
(121 reference statements)
11
57
0
Order By: Relevance
“…Moreover, NPH3, which is essential for phototropism in etiolated and green seedlings (Motchoulski and Liscum, 1999; Goyal et al, 2016) was also required for the response in our conditions (Figure 3B). One of the first steps in phot1 signaling is NPH3 de-phosphorylation, which was recently implicated in modulating the phototropic response as reduced NPH3 de-phosphorylation correlates with accelerated phototropism in seedlings treated for a few hours with light prior to phototropic stimulation (Sullivan et al, 2019). We therefore tested whether the LBL treatment that accelerates phototropism led to changes in NPH3 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NPH3, which is essential for phototropism in etiolated and green seedlings (Motchoulski and Liscum, 1999; Goyal et al, 2016) was also required for the response in our conditions (Figure 3B). One of the first steps in phot1 signaling is NPH3 de-phosphorylation, which was recently implicated in modulating the phototropic response as reduced NPH3 de-phosphorylation correlates with accelerated phototropism in seedlings treated for a few hours with light prior to phototropic stimulation (Sullivan et al, 2019). We therefore tested whether the LBL treatment that accelerates phototropism led to changes in NPH3 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…In the conditions we tested phot1 is the primary photoreceptor controlling hypocotyl reorientation and the enhanced response of cry1 mutants depends on phot1 (Figure 3). In seedlings treated with a few hours of light to initiate de-etiolation NPH3 phosphorylation has an effect on phototropism (Sullivan et al, 2019). In our conditions, we found that NPH3 is essential for phototropism but we did not detect an effect of LBL on NPH3 phosphorylation (inferred from mobility shifts on SDS-PAGE gels) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Even though phototropism is a phenotypic adaptation seen in multiple organs and stages of plant development, much of our understanding is based on studies using dark-grown (etiolated) seedlings. In this issue of Plant Physiology, Sullivan et al (2019) show that phototropism is much stronger in deetiolated seedlings. They expose dark-grown seedlings to light for 8 h, enough to promote deetiolation: opening, expansion, and greening of cotyledons (Gommers and Monte, 2018).…”
mentioning
confidence: 91%
“…The work of Sullivan et al (2019) unravels an interesting interaction between deetiolation and phototropism. They point out that the difference between light and dark is made at the level of NPH3 phosphorylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation